Health Care Disparities and the Emergency Management of Postpartum Patients with Cardiovascular Complaints - Stafford, Irene A.; Viertel, Valentina G.; Wilken, Lindsay A.; Olmsted, Kaleigh E.; Porter, Mayrose R.; Armstrong, Julia M.; GO, Gabriella; Roberts, Aaron W. (American Journal of Perinatology, 2023)
Objective This study aimed to determine health care disparities in evaluation and admission among underserved racial and ethnic minority groups presenting with cardiovascular complaints during the first postpartum year according to patient and provider demographics.Study Design A retrospective cohort study was performed on all postpartum patients who sought emergency care between February 2012 and October 2020 in a large urban care center in Southeastern Texas. Patient information was collected according to International Classification of Diseases 10th Revision codes and individual chart analysis. Race, ethnicity, and gender information were self-reported for both patients on hospital enrollment forms and emergency department (ED) providers on their employment records. Statistical analysis was performed with logistic regression and Pearson's chi-square test.Results Of 47,976 patients who delivered during the study period, 41,237 (85.9%) were black, Hispanic, or Latina and 490 (1.1%) presented to the ED with cardiovascular complaints. Baseline characteristics were similar between groups; however, Hispanic or Latina patients were more likely to have had gestational diabetes mellitus during the index pregnancy (6.2 vs. 18.3%). There was no difference in hospital admission between groups (17.9% black vs. 16.2% Latina or Hispanic patients). There was no difference in the hospital admission rate by provider race or ethnicity overall (p = 0.82). There was no difference in the hospital admission rate when a patient was evaluated by a provider of a different race or ethnicity (relative risk [RR] = 1.08, CI: 0.6–1.97). There was no difference in the rate of admission according to the self-reported gender of the provider (RR = 0.97, CI: 0.66–1.44).Conclusion This study illustrates that disparities did not exist in the management of racial and ethnic minority groups who presented to the ED with cardiovascular complaints during the first postpartum year. Patient–provider discordance in race or gender was not a significant source of bias or discrimination during the evaluation and treatment of these patients.Key Points
Keywords: disparities; inequities; minorities; underserved; postpartum mortality; pregnancy-related mortality; patient–physician concordance